Pojęcie demona i jego wpływ na interpretację fenomenu opętania. Perspektywa filozoficzna w świetle wybranych autorów - Baranowska, Anna (My University, 2015)
W pracy doktorskiej podjęty został problem wpływu pojęcia na sposób interpretacji i rozumienia fenomenu opętania demonicznego. Problem nakreślony został w filozoficznej perspektywie na podstawie materiału źródłowego dostarczonego przez Apulejusza z Madaury, Orygenesa, św. Augustyna, św. Anzelma, Witelona, św. Tomasza, Z. Freuda oraz C. G. Junga. Wnioski pracy przedstawiają trzy możliwe interpretacje fenomenu opętania: interpretację antropologiczno-kulturową, metafizyczną oraz psychoanalityczną.

The PhD thesis deals with the issue concerning the influence of the word on the way how the phenomenon of demonic possession is interpreted and understood. The issue was framed in a philosophic perspective based on source materials provided by Apuleius Madaurensis, Origne, Saint Augustine, Saint Anselm of Canterbury, Witelo, Thomas Aquinas, S. Freud, and C. G. Jung. The conclusions of the thesis introduce three possible interpretations related to the phenomenon of possession: the cultural anthropological, the metaphysical, and the psychoanalytical interpretations.
The notion of demon and its influence on the interpretation concerning the phenomenon of possession. A philosophical perspective in the light of selected authors
Wydział Teologiczny
Keywords: demon; opętanie demoniczne; interpretation; interpretacja; phenomenon of possession